Effect of Iota Carrageenan Addition on Physical, Chemical, and Hedonic Properties of Dumpling (Siomay) Skin - Widyaningrum, Ratna; Saputra, Eka; Sulmartiwi, Laksmi (Universitas Airlangga, 2024)
Dumpling skin is a processed food that is commonly used as a wrapper in the process of making dumplings or other processed foods. Generally, dumpling skins that are sold in the market are easily torn when processed. On the other hand, carrageenan has been widely used in the food industry as an emulsifier and gelling agent. This study aims to determine the effect of adding carrageenan to the physical, chemical and hedonic properties of siomay dumpling skin. This study used an experimental method and a completely randomized design (CRD) with four treatments and five replications. The results showed that the P0 treatment (without carrageenan) had the best hardness (4247%), springiness (12.03%), gumminess (3.85%), chewiness (3.33%), resilience (2.05%) compared to treat with the addition of carrageenan. Meanwhile, the best viscosity in P3 (addition of 70 g carrageenan) was 38.77%, and cohesiveness in treatment P2 (50 g carrageenan) was 0.94%). The treatment without the addition of carrageenan (P0) had a water content of 27.48%, carbohydrates (63.8%), and fiber 0.52%. Treatment P3 (carrageenan 70 g) had a protein content of 5.77% and fat of 1.35%. Meanwhile, treatment P1 (30 g carrageenan) had an ash content of 2.16%. The results of hedonic analysis showed that treatment P2 (50 g carrageenan) had the best appearance value of 6.25. The best aroma and taste in the treatment without the addition of carrageenan were 6.16 and 6.07 respectively. Meanwhile, the best texture of 6.14 was found in treatments P1 (30 g carrageenan) and P2 (50 g carrageenan).